Key findings on legal and regulatory barriers to HIV testing and access to care across Europe. (28th February 2018) - Power, L; Hows, J; Jakobsen, SF; ,
Abstract : Objective: The aim of this work within OptTEST by HiE has been to demonstrate the role of legal and regulatory barriers in hindering access to HIV testing, treatment and care across Europe and to produce tools to help dismantle them. Methods: An online survey to assess country‐specific data on legal and regulatory barriers distributed widely across the WHO Europe region. Literature reviews conducted in January‐October 2015 in English, in November 2015 in Russian, and updated in April 2017. Semi‐structured interviews were conducted with 25 key actors within the HIV field to feed into case studies and tip sheets on how to dismantle legal and regulatory barriers. Results: More than 160 individuals and organisations from 49 countries across the WHO European region provided responses which were analysed and cross checked with other data sources and a searchable database produced (legalbarriers.peoplewithhiveurope.org). The conducted literature reviews yielded 88 papers and reports which identify legal and regulatory barriers to key populations' access to HV testing and care. Based on the interviews with key actors, ranging from PLHIV activists to government officials, on lessons‐learned, a series of tip sheets and ten case studies were written‐up intended to inform and inspire the HIV community to address and overcome existing barriers (opttest.eu/Tools). Conclusion: While some of the barriers identified may require major changes to wider health systems, or long term legal reform, many are open to a simple change in regulations or custom and practice. We have the tools. Why can't we finish the job?